2006
DOI: 10.1152/japplphysiol.01415.2004
|View full text |Cite
|
Sign up to set email alerts
|

Altered secretion of growth hormone and luteinizing hormone after 84 h of sustained physical exertion superimposed on caloric and sleep restriction

Abstract: The pulsatile release of growth hormone (GH) and luteinizing hormone (LH) from the anterior pituitary gland is integral for signaling secretion of insulin-like growth factor (IGF)-I and testosterone, respectively. This study examined the hypothesis that 84 h of sustained physical exertion with caloric and sleep restriction alters the secretion of GH and LH. Ten male soldiers [22 yr (SD 3), 183 cm (SD 7), 87 kg (SD 8)] had blood drawn overnight from 1800 to 0600 every 20 min for GH, LH, and leptin and every 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 40 publications
4
53
3
1
Order By: Relevance
“…It has, also, been shown that weight reduction may lead to alterations in lipid profile, as it is the case in our study, which may be the consequence of the increased hormonal responses to the exercise. Our data are in agreement with previous studies that showed an increase in testosterone and cortisol immediately after exercise [4,31]. However, Opstad [32] and Axelsson et al [33] found no change in cortisol concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has, also, been shown that weight reduction may lead to alterations in lipid profile, as it is the case in our study, which may be the consequence of the increased hormonal responses to the exercise. Our data are in agreement with previous studies that showed an increase in testosterone and cortisol immediately after exercise [4,31]. However, Opstad [32] and Axelsson et al [33] found no change in cortisol concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…Nindl et al [31] observed that brief periods of intense physical activity superimposed on energy and sleep restriction induced amplifications in GH and LH secretions. However, due to methodological differences such as exercise type (e.g., intensity and duration) or sleep loss protocol, the present study's results cannot be compared with those of previous investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, basal serum cortisol decreased with a concomitant increase in the number of subjects who felt overloaded. Previously, serum total testosterone concentration has been shown to decrease in response to demanding training periods (6,37), as well as during extremely stressful military training periods (25,26), and to increase with overload training (36). In contrast to the present study, basal SHBG has been found to increase (19,23) and IGF-1 to decrease (23-26) after heavy training.…”
Section: Discussioncontrasting
confidence: 93%
“…This may be a marker of overtraining, along with lower psychosocial stress (29,31,33,37). Basal serum cortisol has been found to increase during extremely stressful military training periods (25,26), but no change (6,19,36), or a decrease (29,31) has been observed in endurance based overtraining studies.…”
Section: Discussionmentioning
confidence: 99%
“…While these conventional nutritional biomarkers have their utility, they are limited by their relatively long half-lives (2-20 days) and can be affected by nonnutritional factors (18,25). Unlike many hormones used as biomarkers of nutritional/metabolic status, such as growth hormone (GH), IGF-I concentrations exhibit minimal circadian variability through the day (26); therefore, single time samples are valid indicators of IGF-I status.…”
mentioning
confidence: 99%